Optimasi Lama Fermentasi Isolat Actinomycetes Terhadap Pertumbuhan Trichophyton rubrum Secara In Vitro - Muhammad Faris Faruqi (2023)
Indonesia is a developing country with a tropical climate that supports the growth and development of microorganisms that cause infectious diseases, one of which is fungi. Pathogenic fungi can cause diseases in humans, one of which is dermatophytosis. Dermatophytosis is caused by fungi from the genus Trichophyton. Actinomycetes are Gram-positive bacteria, rod-shaped and form spores, and compared to other bacteria groups, they have a special difference that is producing bioactive compound products that can act as antifungi. The production of antifungal compounds is influenced by the acidity level because Actinomycetes live optimally at pH 6-8, and also different fermentation times although its effectiveness is not directly proportional to the longer fermentation is done. This study used Actinomycetes isolate samples that have successfully been isolated from the soil of the Bogor Botanical Garden. This study used the well diffusion method to test the antifungal activity of isolate samples. The activity of Actinomycetes isolates with fermentation times of 1, 2, and 3 days were able to inhibit the growth of T. rubrum with an average inhibition zone of 8.60 mm; 8.32 mm; and 15.44 mm respectively. The mechanism of inhibiting growth can be inhibiting protein biosynthesis, disrupting the synthesis of the fungal cell wall by inhibiting chitin synthase, and inhibiting trehalose that suppresses the breakdown of intracellular trehalose. The ANOVA test results showed that the most optimal fermentation time in inhibiting the growth of T. rubrum is on day 3 fermentation with a significant difference compared to day 1 and 2